2022
DOI: 10.5194/isprs-archives-xliii-b1-2022-121-2022
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Mobile Mapping Systems and (Bim) Digital Models for Construction Progress Monitoring

Abstract: Abstract. Technological developments of the last decades are making possible to speed up different processes involved in construction projects. It is noticeable what building information modeling (BIM) can offer during the entire lifecycle of a project by integrating graphical and non graphical data, in addition to this, mapping the site with a 3D laser scan has been proved to provide a feasible workflow to compare as built models with as designed BIM, in this way, an automatic construction progress monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the context of studying other sensors such as the Kinect V2 equipped with a light sensor camera, Lachat et al [ 21 ] highlights the influence of defects such as colour and reflectivity where the Kinect is very often affected by factors such as light and colourimetry on the numerisation of artefact. Sgrenzarol et al [ 22 ] has also shown the use of Mobil scan with Indoor Mobile Mapping Systems (iMMs) for monitoring the progress of buildings during the construction phase. Comparisons have been made between the true depth (Artec Space Spider with Blue Light Technology 1) sensor and the handheld scanner of the iPad Pro.…”
Section: State Of Artmentioning
confidence: 99%
“…In the context of studying other sensors such as the Kinect V2 equipped with a light sensor camera, Lachat et al [ 21 ] highlights the influence of defects such as colour and reflectivity where the Kinect is very often affected by factors such as light and colourimetry on the numerisation of artefact. Sgrenzarol et al [ 22 ] has also shown the use of Mobil scan with Indoor Mobile Mapping Systems (iMMs) for monitoring the progress of buildings during the construction phase. Comparisons have been made between the true depth (Artec Space Spider with Blue Light Technology 1) sensor and the handheld scanner of the iPad Pro.…”
Section: State Of Artmentioning
confidence: 99%
“…TLSs are widely used in a variety of applications, including cultural heritage [3,4], change detection [5,6], monitoring and deformation [7][8][9], as-built modelling [10], and forestry [11]. In the late 2000s, mobile mapping systems (MMS), which operate on a vehicle such as a car, were introduced into mapping operations, mainly for data capture on road infrastructure and building facades [12] and extended its use to various applications [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of the Building Information Modelling (BIM) paradigm and the demand for as-built BIM models are growing in Architecture, Engineering and Construction (AEC) industry (Banfi, 2017, Banfi, 2019, being critical for a variety of applications, including as-built vs as-designed analyses, change detection and construction progress monitoring (Previtali et al, 2020, Sgrenzaroli et al, 2022. For existing * Corresponding author buildings, BIM modelling turns into a problem of reverse engineering based on 3D point clouds, referred to as the scanto-BIM process (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%